THE EFFECT OF COMPENSATION ON EMPLOYEE PERFORMANCE WITH WORK DISCIPLINE AS AN INTERVENING VARIABLE FOR OFFICERS CLEANLINESS OF BUPATI SERDANG BEDAGAI - Rudy Sentosa Rajagukguk, Frederick (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
This study aims to determine and analyze the effect of compensation on employee performance with work discipline as an intervening variable for cleaning officers at the Serdang Bedagai Regent's Office. The analytical method used is simple linear regression analysis to test the causal relationship between the causal factors and the effect variables. The results of this study obtained that tcount (4.891) > ttable (1.701), as well as the significance value of 0.000 <0.05, it can be concluded that the first hypothesis is accepted, meaning that compensation(X) has a positive and significant effectto Work Discipline (Z). it is known that tcount (2.502) > ttable (1.701), and the significance value is 0.01 <0.05, it can be concluded that the second hypothesis is accepted, meaning that compensation (X) has a positive and significant effecton Employee Performance (Y). it is known that tcount (2.473) > ttable (1.701), and the significance value is 0.03 <0.05, it can be concluded that the third hypothesis is accepted, meaning Work Discipline (Z)take effectpositive and significanton Employee Performance (Y). Path analysis shows that the direct effect of variable X on variable Y2 is 0.421. Meanwhile, the indirect effect through variable Z is 0.679 x 0.416 = 0.2824. From the calculation results obtained, it shows that the direct effect through the X variable is greater than the indirect effect on the Y variable.